REDEFINISI PENDIDIKAN AGAMA ISLAM DALAM TERANG PENDIDIKAN KARAKTER - Amri Darwis (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2012)
This paper attempts to redefine the concept of Islamic Religious Education (PAI), especially in the field of moral education, which is confronted with the problem in the present context: weak character of the nation. The study is based on these three things: 1) the material of akhlaq is being the public concern, 2) it is also the core of Islamic teachings, and 3) The term „akhlaq‟ experiences limitation in terms of meaning in PAI. The method of discussion used is the philosophical of Islamic education. The data is processed through the discourse analysis, then discussed in accordance with the context and the present needs, and synthesized with actual and universal values of Islamic teachings. The results showed that 1) the core of PAI is building character, not merely teaching rituals, 2) The materials about „akhlak‟ do not cover the contemporary issues such as how Muslims in Indonesia live better as the member of the state and the nation, 3) there is a meaningful relation between ethics, morals and characters in the context of PAI. PAI which is based on akhlak, moral principles and character should consider: 1) integration, 2) relativity, 3) environment, 4) reciprocity, and 5) the relevance or adaptation. The five principles are essentially avoiding the symbolic PAI practices which is formalist, apologetics and fanatical.